DECENTRALIZATION OF PUBLIC ADMINISTRATION AS THE BASIS OF PUBLIC MANAGEMENT AT THE LOCAL LEVEL - Ladonko L.S.; Mykhailovska O.V.; Kundenko A.V. (Pressing Problems of Public Administration, 2016)
The article studies the characteristics of decentralization of public administration in Ukraine as a part of public management on the example of Chernihiv region. The effective forms of cooperation between public bodies of public administration at the local level are considered.